ANALISIS DAMPAK NEGATIF FACEBOOK PADA REMAJA KELAS X IPS SMA KEMALA BHAYANGKARI KUBU RAYA - Malindo, Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The negative impact of the use of facebook is a result caused the use of facebook excessively that can give rise to abuse and diversion to brpengaruh directly to the consumer, and often waste time just to tamper with his facebook account, if not used wisely facebook will have a negative impact to pengggunanya it sendiri..Oleh because the researchers wanted to know more profound analysis of the negative impact on teenagers facebook IPS class X SMA Kemala Bhayangkari Kubu Raya.A common problem in this research is "How does a negative impact on teenagers facebook IPS class X SMA KEMALA Bhayangkari Kubu Raya. Sub-problems: (1) What are the negative effects on teenagers Psychological facebook IPS class X SMA KEMALA Bhayangkari Kubu Raya? (2) What are the negative effects on teenagers facebook Physiological class X IPS SMA Kemala Bhayangkari Kubu Raya? (3) Any negative impact on teenagers facebook Sociological class X IPS SMA Kemala Bhayangkari Kubu Raya?The research variables are facebook negative impact on teenagers. The method used is descriptive method with quantitative approach to shape analysis. This research sample numbering 69 classes X IPS SMA Bhayangkari Kubu Raya. Data collection techniques in this study is the technique of indirect communication, data collection tool was a questionnaire. The data were analyzed by calculating the percentage. Based on the analysis of negative effects on teenagers facebook IPS class X SMA Kemala Bhayangkari Kubu Raya as a whole reached 65% by the category of "Low". Keywords: Negative Impact, Facebook, Teens